Strength Analysis of Metro Capsuleâs Bogie Component - Azarya Harjandi, Yosua
Number of vehicle’s growth is not followed by the extension of roads in Bandung city, as a result the traffic in Bandung city increase. One of the solution to solve that problem is applying public transportation model such as Metro Kapsul. In order to ensure the operation safety of Metro Kapsul, strength analysis of Metro Kapsul’s bogie component is done. Three critical components of Metro Kapsul bogie are knuckle plate, tie rod and guide wheel shaft. The components are functioned to transfer forces from the bogie to wheel which allow Metro Kapsul to travel around corner. The purpose of this research is determining stress and safety factor of knuckle plate, tie ro and guide wheel shaft. In additional, fatigue safety factor is also measured. The safety factor is determined based on Regulation of the Minister of Transportation No 175 of 2015 for all three components while UIC 615-4 standard used for knuckle plate. The analysis is conducted using ANSYS with Finite Element Method which has three cases of force distribution. First, transient phase which occurs when Metro Kapsul is about entering the corner while there is movement of bogie components. Second, steady-state phase when Metro Kapsul is cornering perfectly but there is no movement of bogie components. Third, the phase based on UIC 615-4 code when the Metro Kapsul is stationary. The result of maximum equivalent stress analysis and safety factor on knuckle plate are 195,64 MPa and 2,68 for the first phase. 164,06 MPa and 3,20 for the second phase, and 188,69 MPa and 2,78 for UIC 615-4 phase. On the other hand, maximum equivalent stress and safety factor on tie rod are 118,56 MPa and 4,42 while guide wheel shaft are 225,35 MPa and 1,45. Based on the result, knuckle plate, tie rod and guide wheel shaft meet the requirement of Regulation of the Minister of Transportation No 175 of 2015 since none of the maximum equivalent stresses exceed 75% of material’s yield strength. Moreover based on Modified Goodman fatigue failure criteria, knuckle plate, tie rod, guide wheel shaft is proved to be safe.